2012
DOI: 10.1017/jfm.2012.72
|View full text |Cite
|
Sign up to set email alerts
|

Where do small, weakly inertial particles go in a turbulent flow?

Abstract: We report experimental results on the dynamics of heavy particles of the size of the Kolmogorov scale in a fully developed turbulent flow. The mixed Eulerian structure function of two-particle velocity and acceleration difference vectors was observed to increase significantly with particle inertia for identical flow conditions. We show that this increase is related to a preferential alignment between these dynamical quantities. With increasing particle density the probability for those two vectors to be collin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…In homogeneous turbulence the mechanism of preferential concentration causes the inertial particles to be in regions of low enstrophy and high strain (Squires & Eaton 1991;Gibert et al 2012). This is confirmed also for the considered flow in figure 8, that displays the joint PDF of normalized particle concentration C/C o and fluid enstrophy ξ /ξ o , where ξ is the fluid enstrophy.…”
Section: Particle Distributionsupporting
confidence: 68%
See 1 more Smart Citation
“…In homogeneous turbulence the mechanism of preferential concentration causes the inertial particles to be in regions of low enstrophy and high strain (Squires & Eaton 1991;Gibert et al 2012). This is confirmed also for the considered flow in figure 8, that displays the joint PDF of normalized particle concentration C/C o and fluid enstrophy ξ /ξ o , where ξ is the fluid enstrophy.…”
Section: Particle Distributionsupporting
confidence: 68%
“…Particles of St η = 1 also display maximum dispersion rates and maximum time rate of change of their temperature fluctuations (Wetchagarun & Riley 2010). In the last decade, experimental, numerical and theoretical studies have deepened our understanding of the origins of turbulence clustering (Goto & Vassilicos 2008;Salazar et al 2008;Gibert, Xu & Bodenschatz 2012;Bragg & Collins 2014), its consequences on the statistics of particle motion (Ayyalasomayajula et al 2006;Bec et al 2006) and on the particle collision rate (Sundaram & Collins 1997;Wang, Wexler & Zhou 2000).…”
mentioning
confidence: 99%
“…Specifically, techniques for Lagrangian tracking of particles in turbulent flows have provided new perspectives on the behavior of inertial particles in turbulence (Ayyalasomayajula et al, 2006;Gibert et al, 2012;Bewley et al, 2013). Of course, there are deviations from idealized flow conditions achievable in a laboratory setting: for example, boundary conditions vary in time so that quasi-stationary conditions must be sought.…”
Section: Discussionmentioning
confidence: 99%
“…The range of turbulence intensities over which these small animals remain able to perform some of the striking behavioural features that they display in still water, for instance trail-following behaviour, is also worth exploring. In a turbulent flow, particles with small to moderate inertia and size below or equal to the Kolmogorov length scale tend to move preferentially to regions of low vorticity and high strain [81]. Because in these regions peak density of particles can be much higher than the mean value [82], it was suggested that preferential concentrations can increase copepod encounter rates in the ocean [62].…”
mentioning
confidence: 99%